Branding Images and Customer Relationship Management (CRM) in Islamic Educational Institutions: A Case Study of Private Schools - Iskandar, Khusnan (Academia Publication, 2024)
This research article aims to analyse the role of branding images and Customer Relationship Management (CRM) in strengthening the quality of education in Islamic schools. The research uses a qualitative descriptive approach, conducted at Khadijah High School in Surabaya. Data was collected through observation, in-depth interviews, and documentation, then analysed descriptively while maintaining data validity through source and technique triangulation. The results show that branding images are built through consistency in institutional identity, academic reputation, quality of educational services, and the strengthening of religious values, which contribute to increased public trust and interest. CRM is implemented through the management of ongoing relationships with students, parents, alumni, and the community, thereby encouraging stakeholder satisfaction and loyalty. The synergy between branding images and CRM has proven to have a positive impact on the sustainable strengthening of Islamic education quality. These findings confirm that the integration of branding and customer relationship management strategies is an effective approach to improving the competitiveness and sustainability of Islamic educational institutions.